Implementasi Praktik Etika Batuk Yang Benar Dan Baik Dalam Preventif Penyakit Tb Paru - Sallo, Andi Kamal M.; Sahalessy, Yona; Malaha, Naomi; Subani, Natalia Debi; Purwanto, Medy; Puspitarini, Nurul Aisyiyah; Rosmiati, Rosmiati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Eradication of Pulmonary TB is an effort that is greatly influenced by several factors including the attitude of health workers in treating patients, the availability of drugs and the patient's own factors. The main objective of cough etiquette is to prevent the spread of diseases caused by aerosols and to describe the knowledge, attitudes and actions of cough etiquette in tuberculosis patients. The research method is quantitative descriptive with the population of all pulmonary tuberculosis patients and sample selection using total sampling techniques with data collection techniques using questionnaires and observation sheets. The data analysis used is frequency distribution. The results of the pretest of the level of knowledge of participants about good and correct cough etiquette, the most of which was poor knowledge of 24 people (55.9%), while after being given education in the form of health counseling, there was an increase in participant knowledge to a level of sufficient knowledge of 19 people (48.8%). The conclusion is that the behavior of preventing transmission is included in health behavior which is influenced by 3 domains, namely knowledge, attitudes and practices/actions. One of the components in the behavior of preventing TB transmission is implementing good and correct cough etiquette.